Multimodal Discourse Analysis and Electronic Devices: A Pilot Study on Emotionally Supported Evidence. - PALMER-SILVEIRA, JUAN CARLOS; RUIZ-GARRIDO, MIGUEL F. (Atlantis (0210-6124), 2024)
Communication is multimodal in its very nature. In recent decades, research interest in this topic has grown exponentially, especially from a Multimodal Discourse Analysis (MDA) standpoint. Within academic settings, several studies have looked at lecturers' combinations of verbal and non-verbal features, but not necessarily in relation to the emotions that are implicitly part of lecturing. We believe that teaching involves transmitting knowledge together with emotions to students, more or less consciously. This may even be more relevant in an English Medium Instruction (EMI) setting, as English is not the instructor's main language. Thus, our main aim is to analyse an example of EMI teaching practice from an MDA perspective but adding an electronic device--an electroencephalograph--that can help us improve and/or complement the analysis in different ways: adding more objective support and dealing with the emotions lecturers can transmit when delivering their classes. Results show that this combination of observation and technology can potentially enrich results from traditional MDA research.